Integral of sin2x*sinx*cos3x dx
The solution
Detail solution
-
There are multiple ways to do this integral.
Method #1
-
The integral of a constant times a function is the constant times the integral of the function:
∫2sin2(x)cos(x)cos(3x)dx=2∫sin2(x)cos(x)cos(3x)dx
-
Rewrite the integrand:
sin2(x)cos(x)cos(3x)=4sin2(x)cos4(x)−3sin2(x)cos2(x)
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫4sin2(x)cos4(x)dx=4∫sin2(x)cos4(x)dx
-
Rewrite the integrand:
sin2(x)cos4(x)=(21−2cos(2x))(2cos(2x)+21)2
-
Let u=2x.
Then let du=2dx and substitute du:
∫(−16cos3(u)−16cos2(u)+16cos(u)+161)du
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−16cos3(u))du=−16∫cos3(u)du
-
Rewrite the integrand:
cos3(u)=(1−sin2(u))cos(u)
-
Let u=sin(u).
Then let du=cos(u)du and substitute du:
∫(1−u2)du
-
Integrate term-by-term:
-
The integral of a constant is the constant times the variable of integration:
∫1du=u
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−u2)du=−∫u2du
-
The integral of un is n+1un+1 when n=−1:
∫u2du=3u3
So, the result is: −3u3
The result is: −3u3+u
Now substitute u back in:
−3sin3(u)+sin(u)
So, the result is: 48sin3(u)−16sin(u)
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−16cos2(u))du=−16∫cos2(u)du
-
Rewrite the integrand:
cos2(u)=2cos(2u)+21
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(2u)du=2∫cos(2u)du
-
Let u=2u.
Then let du=2du and substitute 2du:
∫4cos(u)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(u)du=2∫cos(u)du
-
The integral of cosine is sine:
∫cos(u)du=sin(u)
So, the result is: 2sin(u)
Now substitute u back in:
2sin(2u)
So, the result is: 4sin(2u)
-
The integral of a constant is the constant times the variable of integration:
∫21du=2u
The result is: 2u+4sin(2u)
So, the result is: −32u−64sin(2u)
-
The integral of a constant times a function is the constant times the integral of the function:
∫16cos(u)du=16∫cos(u)du
-
The integral of cosine is sine:
∫cos(u)du=sin(u)
So, the result is: 16sin(u)
-
The integral of a constant is the constant times the variable of integration:
∫161du=16u
The result is: 32u−64sin(2u)+48sin3(u)
Now substitute u back in:
16x+48sin3(2x)−64sin(4x)
So, the result is: 4x+12sin3(2x)−16sin(4x)
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−3sin2(x)cos2(x))dx=−3∫sin2(x)cos2(x)dx
-
Rewrite the integrand:
sin2(x)cos2(x)=(21−2cos(2x))(2cos(2x)+21)
-
Let u=2x.
Then let du=2dx and substitute du:
∫(81−8cos2(u))du
-
Integrate term-by-term:
-
The integral of a constant is the constant times the variable of integration:
∫81du=8u
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−8cos2(u))du=−8∫cos2(u)du
-
Rewrite the integrand:
cos2(u)=2cos(2u)+21
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(2u)du=2∫cos(2u)du
-
Let u=2u.
Then let du=2du and substitute 2du:
∫4cos(u)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(u)du=2∫cos(u)du
-
The integral of cosine is sine:
∫cos(u)du=sin(u)
So, the result is: 2sin(u)
Now substitute u back in:
2sin(2u)
So, the result is: 4sin(2u)
-
The integral of a constant is the constant times the variable of integration:
∫21du=2u
The result is: 2u+4sin(2u)
So, the result is: −16u−32sin(2u)
The result is: 16u−32sin(2u)
Now substitute u back in:
8x−32sin(4x)
So, the result is: −83x+323sin(4x)
The result is: −8x+12sin3(2x)+32sin(4x)
So, the result is: −4x+6sin3(2x)+16sin(4x)
Method #2
-
Rewrite the integrand:
sin(x)sin(2x)cos(3x)=8sin2(x)cos4(x)−6sin2(x)cos2(x)
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫8sin2(x)cos4(x)dx=8∫sin2(x)cos4(x)dx
-
Rewrite the integrand:
sin2(x)cos4(x)=(21−2cos(2x))(2cos(2x)+21)2
-
Let u=2x.
Then let du=2dx and substitute du:
∫(−16cos3(u)−16cos2(u)+16cos(u)+161)du
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−16cos3(u))du=−16∫cos3(u)du
-
Rewrite the integrand:
cos3(u)=(1−sin2(u))cos(u)
-
Let u=sin(u).
Then let du=cos(u)du and substitute du:
∫(1−u2)du
-
Integrate term-by-term:
-
The integral of a constant is the constant times the variable of integration:
∫1du=u
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−u2)du=−∫u2du
-
The integral of un is n+1un+1 when n=−1:
∫u2du=3u3
So, the result is: −3u3
The result is: −3u3+u
Now substitute u back in:
−3sin3(u)+sin(u)
So, the result is: 48sin3(u)−16sin(u)
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−16cos2(u))du=−16∫cos2(u)du
-
Rewrite the integrand:
cos2(u)=2cos(2u)+21
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(2u)du=2∫cos(2u)du
-
Let u=2u.
Then let du=2du and substitute 2du:
∫4cos(u)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(u)du=2∫cos(u)du
-
The integral of cosine is sine:
∫cos(u)du=sin(u)
So, the result is: 2sin(u)
Now substitute u back in:
2sin(2u)
So, the result is: 4sin(2u)
-
The integral of a constant is the constant times the variable of integration:
∫21du=2u
The result is: 2u+4sin(2u)
So, the result is: −32u−64sin(2u)
-
The integral of a constant times a function is the constant times the integral of the function:
∫16cos(u)du=16∫cos(u)du
-
The integral of cosine is sine:
∫cos(u)du=sin(u)
So, the result is: 16sin(u)
-
The integral of a constant is the constant times the variable of integration:
∫161du=16u
The result is: 32u−64sin(2u)+48sin3(u)
Now substitute u back in:
16x+48sin3(2x)−64sin(4x)
So, the result is: 2x+6sin3(2x)−8sin(4x)
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−6sin2(x)cos2(x))dx=−6∫sin2(x)cos2(x)dx
-
Rewrite the integrand:
sin2(x)cos2(x)=(21−2cos(2x))(2cos(2x)+21)
-
Let u=2x.
Then let du=2dx and substitute du:
∫(81−8cos2(u))du
-
Integrate term-by-term:
-
The integral of a constant is the constant times the variable of integration:
∫81du=8u
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−8cos2(u))du=−8∫cos2(u)du
-
Rewrite the integrand:
cos2(u)=2cos(2u)+21
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(2u)du=2∫cos(2u)du
-
Let u=2u.
Then let du=2du and substitute 2du:
∫4cos(u)du
-
The integral of a constant times a function is the constant times the integral of the function:
∫2cos(u)du=2∫cos(u)du
-
The integral of cosine is sine:
∫cos(u)du=sin(u)
So, the result is: 2sin(u)
Now substitute u back in:
2sin(2u)
So, the result is: 4sin(2u)
-
The integral of a constant is the constant times the variable of integration:
∫21du=2u
The result is: 2u+4sin(2u)
So, the result is: −16u−32sin(2u)
The result is: 16u−32sin(2u)
Now substitute u back in:
8x−32sin(4x)
So, the result is: −43x+163sin(4x)
The result is: −4x+6sin3(2x)+16sin(4x)
-
Add the constant of integration:
−4x+6sin3(2x)+16sin(4x)+constant
The answer is:
−4x+6sin3(2x)+16sin(4x)+constant
The answer (Indefinite)
[src]
/ 3
| x sin (2*x) sin(4*x)
| sin(2*x)*sin(x)*cos(3*x) dx = C - - + --------- + --------
| 4 6 16
/
∫sin(x)sin(2x)cos(3x)dx=C−4x+6sin3(2x)+16sin(4x)
The graph
cos(1)*cos(2)*cos(3) cos(1)*sin(2)*sin(3) cos(2)*sin(1)*sin(3) cos(1)*cos(3)*sin(2) cos(3)*sin(1)*sin(2) cos(1)*cos(2)*sin(3) 5*sin(1)*sin(2)*sin(3)
- -------------------- - -------------------- - -------------------- - -------------------- + -------------------- + -------------------- + ----------------------
4 4 4 8 4 6 24
4sin(1)sin(2)cos(3)−4cos(1)cos(2)cos(3)−4sin(2)sin(3)cos(1)+6sin(3)cos(1)cos(2)−4sin(1)sin(3)cos(2)+245sin(1)sin(2)sin(3)−8sin(2)cos(1)cos(3)
=
cos(1)*cos(2)*cos(3) cos(1)*sin(2)*sin(3) cos(2)*sin(1)*sin(3) cos(1)*cos(3)*sin(2) cos(3)*sin(1)*sin(2) cos(1)*cos(2)*sin(3) 5*sin(1)*sin(2)*sin(3)
- -------------------- - -------------------- - -------------------- - -------------------- + -------------------- + -------------------- + ----------------------
4 4 4 8 4 6 24
4sin(1)sin(2)cos(3)−4cos(1)cos(2)cos(3)−4sin(2)sin(3)cos(1)+6sin(3)cos(1)cos(2)−4sin(1)sin(3)cos(2)+245sin(1)sin(2)sin(3)−8sin(2)cos(1)cos(3)
Use the examples entering the upper and lower limits of integration.